A Survey on Depressive Symptoms and Its Correlates Amongst Physicians in Bangladesh During the COVID-19 Pandemic - Hasan, M. Tasdik; Anjum, Afifa; Biswas, Md. Abdullah Al Jubayer; Hossain, Sahadat; Alin, Sayma Islam; Koly, Kamrun Nahar; Safa, Farhana; Alam, Syeda Fatema; Rafi, Md. Abdur; Podder, Vivek; Hossain, Md. Moynul; Trisa, Tonima Islam; et al. (Frontiers in Psychology, 2022)
Aim The aim of this study was to determine the presence of depressive symptoms and understand the potential factors associated with these symptoms among physicians in Bangladesh during the COVID-19 pandemic. Methods A cross-sectional study using an online survey was conducted in between April 21 and May 10, 2020, among physicians living in Bangladesh. Participants completed a series of demographic questions, COVID-19-related questions, and the Patient Health Questionnaire-9 (PHQ-9). Descriptive statistics (frequency, percentage, mean and standard deviation), test statistics (chi-squared test and logistic regression) were performed to explore the association between physicians’ experience of depression symptoms and other study variables. Stepwise binary logistic regression was followed while conducting the multivariable analysis. Result A total of 390 physicians completed the survey. Of them, 283 (72.6%) were found to be experiencing depressive symptoms. Predictors which were significantly associated with depressive symptoms were gender (with females more likely to experience depression than males), the presence of sleep disturbance, being highly exposed to media coverage about the pandemic, and fear around (a) COVID-19 infection, (b) being assaulted/humiliated by regulatory forces and (c) by the general public, while traveling to and from the hospital and treating patients during the countrywide lockdown. Conclusion The findings of this study demonstrate that there is a high prevalence of depressive symptom among physicians especially among female physicians in Bangladesh during the COVID-19 pandemic. Immediate, adequate and effective interventions addressing gender specific needs are required amid this ongoing crisis and beyond.